Continuous grade rolling. Trends and perspectives of development of technology and equipmen - S. M. Zhuchkov; A. P. Lohmatov; L. V. Kulakov; D. G. Palamar (Литьë и металлургия)
There are examined the different technological processes of endless rolling, stipulating for jump welding of slugs into endless string and direct alignment of the processes of continuous casting of slugs and rolling. There are marked the successes of foreign firms on using of the process of endless rolling in the foundry-rolling units.